The “pipeline” problem in bilateral financial cooperation - Wolfgang Buch (Intereconomics, 1981)
It has been observed since about 1976 that financial commitments to developing countries have been disbursed more slowly than in the past. At the same time there have been increasing complaints from recipients that the commitment, appraisal and disbursement procedures of the donor countries were excessively complicated, resulting in a delay of disbursements. The Western industrialized countries, both individually and jointly in the Development Assistance Committee of the OECD, therefore initiated investigations into the importance to be assigned to this phenomenon as well as into the question of whether there are any possible ways of simplifying the administrative procedures. The following article sums up the results of such a study by the German Institute for Development Policy in respect of the Federal Republic of Germany.
Keywords: 330; Development Assistance